Aesthetic science connecting minds, brains, and experience - Shimamura, Arthur P.; Palmer, Stephen E. (New York : Oxford University Press, 2011)
What do we do when we view a work of art? What does it mean to have an 'aesthetic' experience? Are such experiences purely in the eye of the beholder? This book addresses the nature of aesthetic experience from the perspectives of philosophy psychology and neuroscience.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 19, 2012).
Includes bibliographical references and index.
Keywords: Neuropsychology; Visual perception; Aesthetics -- Psychological aspects